A prospective study of soluble receptor for advanced glycation end products and adipokines in association with pancreatic cancer in postmenopausal women. (23rd March 2018) - White, Donna L.; Hoogeveen, Ron C.; Chen, Liang; Richardson, Peter; Ravishankar, Milan; Shah, Preksha; Tinker, Lesley; Rohan, Thomas; Whitsel, Eric A.; El‐Serag, Hashem B.; Jiao, Li
Abstract: Advanced glycation end products (AGEs) dysregulate adipokines and induce inflammation by binding to their adipocyte receptor (RAGE). Soluble RAGE (sRAGE) prevents AGEs/RAGE signaling. We performed a nested case–control study of the association between sRAGE, adipokines, and incident pancreatic cancer risk in the prospective Women's Health Initiative Study. We individually matched controls ( n  = 802) to cases ( n  = 472) on age, race, and blood draw date. We evaluated serum concentrations of sRAGE, adiponectin, leptin, monocyte chemotactic protein 1 (MCP1), and plasminogen activator inhibitor‐1 (PAI1) using immunoassay. We used conditional logistic regression model to estimate adjusted odds ratios (aORs) and 95% confidence intervals (CIs) for pancreatic cancer over biomarker quartiles (Q1–Q4). We used principal component analysis to create two composite biomarkers and performed a confirmatory factor analysis to examine the association between composite biomarker scores (CBS) and pancreatic cancer risk. Baseline serum sRAGE concentrations were inversely associated with pancreatic cancer risk (aORQ4 vs. Q1  = 0.70, 95% CI: 0.50–0.99). High MCP1 (aORQ4 vs. Q1  = 2.55, 95% CI: 1.41–4.61) and the higher CBS including MCP1, PAI1, and leptin (aORQ4 vs. Q1  = 1.82, 95% CI = 1.04–3.18) were also associated with increased pancreatic cancer risk among women with BMI <25 kg/m 2 ( P values for interaction <0.05). We found an inverse association between prediagnostic sRAGE concentrations and risk of incident pancreatic cancer in postmenopausal women. A proinflammatory CBS was associated with increased risk only in women with normal BMI. MCP1 was not modulated by sRAGE. Abstract : Serum concentrations of anti‐inflammatory soluble RAGE were inversely associated with risk of incident pancreatic cancer in postmenopausal women. Chemokine MCP1 and a proinflammatory biomarker score including MCP1, leptin, and PAI1 were associated with increased risk of incident pancreatic cancer among lean women.